Training on Booking Management and Business Analysis of Goat Farming Group in Teunom, Aceh Jaya Regency - Dian Kristanti; Izwar Izwar (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
From this community service activity, the Juang Group as a partner, has the knowledge, ability and can see about the goat fattening business, especially bookkeeping management and business/marketing analysis and promotion so that they are independent during this covid pandemic, and have an impact on the quality of life of partners, in terms of economy, health, family education and others. Problems faced by the Juang Group, The accounting management aspect of the partner group is still traditional, Has never made financial books, so that business planning is not based on financial data of real business activities, the solution is to provide training and direct assistance on the cash recording/bookkeeping mechanism. In the aspect of the marketing system and product promotion, they still rely on word of mouth strategies, and do not yet have the ability to use the internet as a media promise. The solution provides training and facilitates the creation of websites and other online media. The Juang Group can implement strategic segmentation, targeting and positioning, as well as being able to conduct market and competition analysis, thus forming a long-term partner network in Aceh Jaya, Aceh Province and other target markets. Keywords: Bookkeeping Management, Business Analysis, Teunom, Goat Farming